2016
DOI: 10.1007/s00330-016-4275-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of 320-row area detector CT coronary angiography using 40 mL of contrast material: assessment of image quality and diagnostic accuracy

Abstract: • 320-ADCT might enable reduction of contrast material volume. • A 40-mL contrast protocol for 320-ADCT provided acceptable image quality. • A 40-mL contrast protocol for 320-ADCT demonstrated sufficient diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It is important to note that with the introduction of novel CT technologies, the amount of CM needed to achieve diagnostic quality has markedly decreased. In a recently published study by Kim et al, CM volume usage in coronary CTA performed with 320-row CT could be decreased from 60 to 40 ml with preserved image quality and diagnostic accuracy [ 16 ]. In addition, Felmly et al demonstrated that with the latest generation dual source CT a comprehensive transcatheter aortic valve replacement planning was feasible with reduced CM volumes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that with the introduction of novel CT technologies, the amount of CM needed to achieve diagnostic quality has markedly decreased. In a recently published study by Kim et al, CM volume usage in coronary CTA performed with 320-row CT could be decreased from 60 to 40 ml with preserved image quality and diagnostic accuracy [ 16 ]. In addition, Felmly et al demonstrated that with the latest generation dual source CT a comprehensive transcatheter aortic valve replacement planning was feasible with reduced CM volumes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[15]. Even less than 60 mL may be appropriate for newer wide-detector CT scanners [16,17]. Iterative reconstruction techniques and low tube potential (70-100 kV) have also favored a reduction in contrast dose.…”
Section: Radiation Exposure and Principle Cardiac Ct-related Risksmentioning
confidence: 99%
“…Moreover, simultaneous developments in the iterative reconstruction technique in combination with low tube potential (70–100 kV) acquisition have contributed to a reduction in contrast material volume. Several researchers have reported the feasibility of using a lower volume (less than 60 mL) of contrast material in wide-detector CT scanners (131415). In 2011, Kumamaru et al (13) compared the image quality between the 60-mL and 80-mL contrast material injection protocols for CCTA by using 320-detector-row CT, and they reported that 96% of the coronary segments showed sufficient enhancement (> 300 Hounsfield units [HU]) when using the 60-mL protocol, thus supporting the general use of 60-mL protocols for clinical wide-area-detector CCTA.…”
Section: Technical Aspects Of the Wide-detector Ct Scanner Systemmentioning
confidence: 99%
“…Hein et al (14) reported the diagnostic image quality achieved using 40 mL of contrast material in prospective ECG-triggered CCTA with a 320-detector-row CT scanner; however, they only enrolled patients with body weight ≤ 85 kg, normal cardiac function, and low heart rate (≤ 65 beats per minute [bpm]). Several years later, Kim et al (15) reported that 320-detector-row CCTA with the 40-mL contrast material protocol showed comparable image quality and diagnostic accuracy to the conventional 60-mL protocol irrespective of patient-related factors; they applied an iterative reconstruction technique (AIDR 3D; Canon Medical Systems), tailored tube voltages (80, 100, and 120 kVp), and tailored contrast injection, which enabled manually-triggered scan commencement by an experienced operator. Nevertheless, optimal enhancement of the coronary arteries for accurate evaluation of coronary arterial stenosis or plaque characterization remains a matter of debate (161718).…”
Section: Technical Aspects Of the Wide-detector Ct Scanner Systemmentioning
confidence: 99%
See 1 more Smart Citation